A Message from the Incoming Editor Team. Issue 3 (15th September 2015) - Goldsby, Thomas J.; Zinn, Walter
Abstract : A transition in editor teams will occur at the Journal of Business Logistics before the end of the year. This brief editorial addresses vital facets of the transition. We emphasize the importance of maintaining the journal's key traditions, namely publishing applied logistics and supply chain research yielding meaningful managerial implications. We speak to remaining open to diverse research questions and assorted research methods, while emphasizing the imperative for state‐of‐the‐art application of methods. Next, we iterate important aspects of the journal's review process. The provision of timely, knowledgeable, constructive, and detailed reviews is underscored as essential to assuring JBL's reputation as the "journal of choice" for leading‐edge logistics and supply chain research.